2009
DOI: 10.1523/jneurosci.5546-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

TMEM16B, A Novel Protein with Calcium-Dependent Chloride Channel Activity, Associates with a Presynaptic Protein Complex in Photoreceptor Terminals

Abstract: Photoreceptor ribbon synapses release glutamate in response to graded changes in membrane potential evoked by vast, logarithmically scalable light intensities. Neurotransmitter release is modulated by intracellular calcium levels. Large Ca 2ϩ -dependent chloride currents are important regulators of synaptic transmission from photoreceptors to second-order neurons; the molecular basis underlying these currents is unclear. We cloned human and mouse TMEM16B, a member of the TMEM16 family of transmembrane proteins… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
192
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(209 citation statements)
references
References 39 publications
14
192
1
2
Order By: Relevance
“…Consistent with previous data [21][22][23] , western blots indicated that Ano2 is most highly expressed in olfactory epithelium (MOE and VNO) and eye tissue (Fig. 1a,b).…”
Section: Disruption Of Ano2 and Ano2 Expression Patternsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous data [21][22][23] , western blots indicated that Ano2 is most highly expressed in olfactory epithelium (MOE and VNO) and eye tissue (Fig. 1a,b).…”
Section: Disruption Of Ano2 and Ano2 Expression Patternsupporting
confidence: 92%
“…Our N-terminal antibody did not detect a truncated protein in Ano2 -/-tissue, suggesting the occurrence of nonsensemediated mRNA decay, instability of the truncated protein, or both. Ano2 -/-mice were born at Mendelian ratio; they grew, mated, and survived normally and lacked an immediately apparent phenotype.Consistent with previous data [21][22][23] , western blots indicated that Ano2 is most highly expressed in olfactory epithelium (MOE and VNO) and eye tissue (Fig. 1a,b).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…2011) and photoreceptors (Stohr et al . 2009), apparently has a different Ca 2+ source preference as compared to ANO1. Huang and colleagues (Huang et al .…”
Section: Activation Of Ano‐mediated Caccs By Localized Ca2+ Signals Imentioning
confidence: 98%
“…2009; Stohr et al . 2009) subunits identified as bona fide CaCCs (see Pedemonte & Galietta, 2014 for review). For example, ANO1 (TMEM16A), reconstituted in an expression system, reproduced key features of native CaCC currents such as higher permeability to I − over Cl − , micromolar Ca 2+ sensitivity, outwardly rectifying voltage dependence and sensitivity to the CaCC blockers 5‐nitro‐2‐(3‐phenylpropylamino)benzoic acid (NPPB), niflumic acid (NFA) and 4,4′‐diisothio‐cyanostilbene‐2,2′‐disulfonic acid (DIDS) (Hartzell et al .…”
Section: Introductionmentioning
confidence: 99%